Analysis of Financial Statements in Assessing Company Financial Performance in the Automotive Sector Registered on the IDX (PT. Astra Internasional Tbk) - Fattah Jati Pangestu; Katarina Watini (PT FORMOSA CENDEKIA GLOBAL, 2022)
The purpose of this study was to determine the financial performance of one of the companies in the automotive sector, namely PT. Astra International Tbk. The company's financial performance was analyzed using the ratio quantitative method on secondary data from the 2017 to 2021 annual financial statements. The ratio analysis used included profitability ratios, liquidity ratios, solvency ratios and activity ratios. The results of the ratio analysis of the financial statements of PT. Astra International Tbk in 2017-2021 shows that the company's financial performance in profitability, liquidity and activity has not reached the industry standard ratio for the last 5 (five) years due to a decline in sales figures, further strategies are needed in an effort to increase sales figures. Solvency of PT. Astra International Tbk is considered good because the ratio is greater than the industry standard ratio. The financial performance in fulfilling the company's long-term obligations was carried out well.